2006
DOI: 10.2134/agronj2005.0094
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Use of Tebuconazole and Fusarium Head Blight–Resistant Barley Genotypes

Abstract: All malting barley (Hordeum vulgare L.) cultivars adapted for production in the upper midwestern USA are susceptible to Fusarium head blight (FHB), incited primarily by Fusarium graminearum Schwabe [teleomorph Gibberella zeae (Schwein)]. Quality of FHB‐infected barley is reduced due to a mycotoxin called deoxynivalenol (DON) that is produced by the pathogen. Malting barley buyers severely discount or refuse to purchase barley with DON concentrations >0.5 mg kg−1. Individually, use of genetic resistance or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Although MS_UT generally had the lowest within-trial rank, there was a collection of environments (trial numbers 9,11,16,17,18,19,20,21,23,24,45, and 46, mostly from Maryland and Missouri) where S_TR had the lowest rank. Many of these trials also had large ranks for MR_UT (which, overall, had an intermediate rank).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although MS_UT generally had the lowest within-trial rank, there was a collection of environments (trial numbers 9,11,16,17,18,19,20,21,23,24,45, and 46, mostly from Maryland and Missouri) where S_TR had the lowest rank. Many of these trials also had large ranks for MR_UT (which, overall, had an intermediate rank).…”
Section: Resultsmentioning
confidence: 98%
“…In general, combining an appropriately timed fungicide application with a moderately resistant cultivar usually results in the greatest reductions in disease intensity and toxin accumulation (46). However, the reported efficacy of this approach in terms of percent reduction in FHB and DON has varied among individual integrated management trials (9,45,46). In addition, results from some trials have shown that, under certain conditions, cultivar resistance or fungicide treatment alone may provide levels of FHB and DON reduction comparable with that of the resistance-fungicide management combination (44,46).…”
mentioning
confidence: 99%
“…The highest DON concentration observed in this study was 0.5 mg kg (McMullen et al 1997;Tekauz et al 2000). The disease reduces yield and results in poor seed quality, which has a negative impact on the market value of the grain and on seed vigour (Horsley et al 2006). In addition, the disease causes kernel contamination with mycotoxins, such as deoxynivalenol (DON) and nivalenol (Campbell et al 2002;Müeller et al 1997), which are harmful to humans and livestock.…”
mentioning
confidence: 79%
“…Grain contamination with DON is a food and feed concern in many countries around the world (Campbell et al 2002;Placinta et al 1999). Furthermore, the malting and brewing industries reject grain with even minute amounts of DON because of quality issues with the resulting malt and beer (Beattie et al 1998;Horsley et al 2006).…”
mentioning
confidence: 99%
“…In contrast, Mesterhazy et al (13) found that fungicide efficacy in controlling FHB and DON accumulation was greater in more resistant than in more susceptible winter wheat cultivars. Horsley et al (6) applied tebuconazole to 13 barley genotypes with varying levels of FHB resistance. They found the response to tebuconazole of moderately resistant genotypes to be inconsistent for FHB severity and DON accumulation.…”
mentioning
confidence: 99%